Study of the Effect of Substituents of ortho-Phenylenediamines in the Opening of Lactones and Lactams for Access to Benzimidazol-2-yl Alkanols and Benzimidazol-2-yl Alkylamines - Castillo-Aguilera, Omar; Depreux, Patrick; Ballée, Alexia; Beaurain, Florian; Arimondo, Paola B.; Goossens, Laurence (Synlett, 2020)
Benzimidazoles represent common chemical moieties in bioactive compounds. The synthesis of this heterocycle often involves a condensation of an ortho-phenylenediamine with a carboxylic acid derivative. The observed dialkylation of the starting ortho-phenylenediamine is avoided by opening of lactones or lactams. This strategy can directly yield 1H-benzimidazoles substituted at the 2-position by a functionalized chain. We present herein a study of the effect of different electron-withdrawing or electron-donating groups at the 4-position of ortho-phenylenediamines on the opening of lactones or lactams to synthesize benzimidazol-2-yl alkanols and benzimidazol-2-yl alkylamines.
Keywords: 2-benzimidazol-2-yl alkanols; 2-benzimidazol-2-yl alkylamines; ortho-phenylenediamines; lactones; lactams